Challenges and possibilities for re-wilding education policy in Japan. Issue 3 (April 2021) - Oguri, Yuko; Takano, Takako
This paper discusses human relationships with the natural world in Japanese educational policy. Based on two case studies, we argue that policy must recognize the cultural and spiritual ties that people in Japan have fostered in order to live well, which this paper considers to be part of "re-wilding education policy." We briefly review the history of educational policy in Japan and identify its core features before clarifying the existing power structure between national and local governments regarding such policy. We also describe the characteristics of the Japanese education system, which stem partly from tensions between central and local governments due to the interpretation of legal frameworks. Through two case studies—situated in a traditional farming community in a mountainous area, and a community on a group of remote islands—this paper focuses on educational practices derived not from the dominant education policy but from local realities. These two cases allow us to demonstrate effective efforts made in these communities to rebuild traditional human–nature relationships on a small scale based on the everyday lives of the inhabitants. We conclude that any successful re-wilding of education policy in Japan will depend on the central government's release of power, recognition of the unique features of diverse localities in Japan, and support for spontaneous activities emerging in local communities.